A Giant Dissecting Aneurysm of Ascending Aorta Following Aortic Valve Replacement - Faruk Hökenek; Mete Gürsoy; Füsun Gülcan; Egemen Duygu; Murat Şener (Case Reports in Medicine)
Ascending aortic dissection and aneurysm are rare but life-threatening complications after aortic valve replacement. Preoperative evaluation of risk factors such as aortic diameter, structural features of aortic wall, and associated diseases may decrease complication rate. We herein present analysis of risk factors of proximal aortic events following aortic valve replacement based on patient with giant dissecting aneurysm who underwent modified Bentall procedure.